2013
DOI: 10.1002/ps.3584
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spray angle and spray volume on deposition of a medium droplet spray with air support in ivy pot plants

Abstract: Spray deposition can be improved hugely simply by changing some spray boom settings like nozzle type, angling the spray, using air support and adjusting the spray volume to the crop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Foqué et al 43 concluded that angling the spray did not result in a higher deposition or penetration capacity compared with the standard vertical spray boom. However, later research carried out by the same authors 30 found a positive trend from using a forward spray angle.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Foqué et al 43 concluded that angling the spray did not result in a higher deposition or penetration capacity compared with the standard vertical spray boom. However, later research carried out by the same authors 30 found a positive trend from using a forward spray angle.…”
Section: Discussionmentioning
confidence: 90%
“…Self-propelled and autonomous sprayers have also attracted interest because of reduced operator exposure, 19,26,27 improved work capacity 19,22 and in some cases reduced application of PPPs while maintaining the efficacy of pest/disease control. 28,29 However, problems have also been reported: poor penetration capacity exhibited by vertical boom sprayers without air assistance; 28,30 management of hand-held trolleys depending on the soil type and sprayer design; difficulties of identifying accurate conditions for safe and efficient use of self-propelled sprayers, including aspects related to the high level of investment required. 16 The objective of this study was to improve the spray application process in Spanish greenhouses by modifying and improving an existing spray technology.…”
Section: -13mentioning
confidence: 99%
“…For the deposition data, the Shapiro–Wilk normality test was used to check whether the data were normally distributed. The Kruskal–Wallis test was used as no suitable way was found to transform the data into a normally distributed dataset 27,28 . The effect of the different application techniques was tested for the different sampling layers and points.…”
Section: Methodsmentioning
confidence: 99%
“…The Kruskal-Wallis test was used as no suitable way was found to transform the data into a normally distributed dataset. 27,28 The effect of the different application techniques was tested for the different sampling layers and points. For the droplet size data, the Shapiro-Wilk normality test proved that the droplet size dataset was not normally distributed.…”
Section: Statistical Data Analysismentioning
confidence: 99%
“…(i) the application technique used (Foqué et al, 2014), (ii) the canopy type and height (Hoffmann et al, 2007), (iii) meteorological conditions (Miller et al, 2011) and (iv) the physiochemical properties of the spray material being applied Hilz & Vermeer, 2013).…”
Section: Introductionmentioning
confidence: 99%